Projected West Antarctic Ocean Warming Caused by an Expansion of the Ross Gyre. Issue 6 (21st March 2023) - Gómez‐Valdivia, Felipe; Holland, Paul R.; Siahaan, Antony; Dutrieux, Pierre; Young, Emma
Abstract: We use United Kingdom Earth System Model simulations from the Coupled Model Intercomparison Project 6 to analyze the Ross Gyre (RG) dynamics during the historical 1850–2014 period and under two contrasting future climate‐change scenarios. The modeled RG is relatively stable, with an extent and strength that agree with observations. The projections exhibit an eastward gyre expansion into the Amundsen‐Bellingshausen Seas that starts during the 2040s. The associated cyclonic ocean circulation enhances the onshore transport of warm Circumpolar Deep Water into the inner regional shelf, a regime change that increases the local subsurface shelf temperatures by up to 1.2°C and is independent of future forcing scenario. The RG expansion is generated by a regional ocean surface stress curl intensification associated with anthropogenic sea ice loss. If realised in reality, such a warming would strongly influence the future stability of the West Antarctic Ice Sheet. Plain Language Summary: We use a climate model to analyze ocean changes around West Antarctica. Our results reveal a human‐driven ocean warming that increases the continental shelf temperature in the Amundsen‐Bellingshausen Seas by more than 1°C in only ∼30 years. This rapid warming is caused by the expansion of the Ross Gyre (RG), a large oceanic circulation in the region. The West Antarctic Ice Sheet is losing mass, causing sea‐level rise, with the most rapid ice losses occurring in the Amundsen‐Bellingshausen Seas. Our results suggest that an expansion of the RG could provide a mechanism whereby melt rates increase far beyond the current range. This could have an important influence on the sea‐level rise caused by this region, with global impacts. Key Points: The UK Earth System Model produces a fairly realistic depiction of ocean conditions in West Antarctica Future projections suggest a rapid warming of the Amundsen Sea induced by a Ross Gyre (RG) expansion that is independent of forcing scenario The RG expansion is primarily caused by a surface stress curl intensification induced by anthropogenic trends in Antarctic sea ice